Earth Resources and Environmental Remote Sensing/Gis Applications IV 2013
DOI: 10.1117/12.2029073
|View full text |Cite
|
Sign up to set email alerts
|

Identification of urban tree crown in a tropical environment using WorldView-2 data: problems and perspectives

Abstract: With the availability of high-resolution satellite data, much research has been focused on the automatic detection and classification of individual tree crowns. Most of these studies were applied to temperate climates of the northern hemisphere, especially for forests of coniferous. Very few studies have been applied to the detection of trees in the tropical regions, least of all in the urban environment. Urban trees play a major role in maintaining or even improving the quality of life in cities by their cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…In the context of ITC detection, TM methods has been exploited in some previous studies [37,52,[99][100][101][102][103][104][105]. A comparative study [52] involving six different ITC detection methods (TM, local maxima, valley following, region-growing, scale-space theory, and techniques based on stochastic frameworks) showed that TM had the best performance among other methods for the detection of isolated tree crowns, which are usually the predominant pattern of trees located in orchards [103].…”
Section: Template Matchingmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of ITC detection, TM methods has been exploited in some previous studies [37,52,[99][100][101][102][103][104][105]. A comparative study [52] involving six different ITC detection methods (TM, local maxima, valley following, region-growing, scale-space theory, and techniques based on stochastic frameworks) showed that TM had the best performance among other methods for the detection of isolated tree crowns, which are usually the predominant pattern of trees located in orchards [103].…”
Section: Template Matchingmentioning
confidence: 99%
“…The position of the occurrence of the best matches on the similarity image indicate the position of the pixels with the highest probability of being a tree crown centroid. Thus, to find the tree crown centroids in the adopted TM algorithm, the NCC values were thresholded (for more details see [52,102,143]). The template match threshold value should be selected with care to meet the requirements of the map users, as setting the threshold value too high leads to a large number of false negative (FN) errors (i.e., undetected tree crowns), while setting the threshold value too low leads to a high number of false positive (FP) errors (i.e., misdetection of non-tree features as tree crowns).…”
Section: Delineation Of Land Parcels In the Test Plotmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of detail in very high spatial resolution sensors, such as WorldView-2, is often appreciated for object detection such as tree crown mapping (e.g. Karlson et al, 2014;Gomes and Maillard, 2013). However, the narrow multispectral bands provide also great potential for robust extraction of forest structural param- eters (Ozdemir and Karnieli, 2011), improved forest biomass and carbon estimations (Eckert, 2012), and to discriminate forest tree species (Peerbhay et al, 2014).…”
Section: Remote Sensing Based Forest Monitoringmentioning
confidence: 99%
“…Further examples of object recognition using satellite and aerial images are aircraft and crater detection [25,26], tree crown detection, oil palm and species detection, and counting in forestry [27][28][29][30][31] and dwelling extraction [32].…”
Section: Introductionmentioning
confidence: 99%